Evaluation of Health Risks Associated with Potential Toxic Elements in Selected Vegetables Consumed in the Western Black Sea Region of Turkey - Aydan Altıkulaç; Şeref Turhan; Ergin Murat Altuner; Barış Şekeroğlu; Aslı Kurnaz (American Chemical Society (ACS), 2025)
Vegetables with useful phytochemicals, vitamins, protein, carbohydrates, and minerals are nutritional sources and play an important role in the prevention of many chronic diseases. However, vegetables are contaminated with potentially toxic elements caused by anthropogenic and natural activities. Therefore, this study is the first attempt to analyze 14 potentially toxic elements in some of the most consumed vegetables in Kastamonu province located in the Western Black Sea Region of Turkey by using an ICP-OES for the evaluation of the potential human health risks of adults due to potentially toxic elements via ingestion. The concentrations (μg/kg, dw) of Fe, Al, Sr, Mn, Zn, Ti, Cu, Ni, Pb, V, As, Cr, Cd, and Co analyzed in sixty-nine samples belonging to thirty-six different vegetable types varied from 3995 to 968073, 569 to 616664, 2730 to 144287, 843 to 51417, 268 to 34344, <LOD to 65115, <LOD to 21506, <LOD to 44230, <LOD to 3671, <LOD to 4582, <LOD to 2996, 198 to 5548, 284 to 1289, and <LOD to 856, respectively. The Pb and Cd concentrations analyzed in the studied vegetable samples were above the maximum levels recommended by the Turkish Food Codex. The hazard index and total cancer risk index were estimated to evaluate noncarcinogenic and carcinogenic health risks, respectively. Evaluation of potential noncarcinogenic risk reveals no risk for consumption of the studied vegetables (except for eggplant, potato, and sugar beet) for adult consumers. However, values of the total cancer risk index estimated for Pb, Ni, Cr, Cd, and As analyzed in 15 vegetable samples are higher than the safety limit (≥10-4).
Keywords: Chemistry; QD1-999